A comparison of stick and slip contact conditions for a coated sphere compressed by a rigid flat - Shai Ronen (Friction, 2017)
Abstract A finite element analysis is used to study the elastic-plastic contact of a coated sphere compressed by a rigid flat under the stick contact condition. This was done for a wide range of hard coating material properties and coating thicknesses. A comparison with the slip contact condition is presented in terms of the critical contact parameters (at yield inception) and plasticity evolution. Empirical expressions are provided for critical interferences of the first and second yield inceptions, in the coating and on the substrate side of the interface, respectively. An expression is also provided for the dimensionless coating thickness for optimal resistance to plasticity under the stick contact condition. Additionally, the relations between different contact parameters in the elastic-plastic regime are presented. In general, it was found that the contact condition has a negligible effect on the contact parameters, except for phenomena occurring close to the contact area.